2017
DOI: 10.13057/oceanlife/o010101
|View full text |Cite
|
Sign up to set email alerts
|

Review: Biology of the commercially used sea urchin Tripneustes gratilla (Linnaeus, 1758) (Echinoidea: Echinodermata)

Abstract: Toha AHA, Sumitro SB, Hakim L, Widodo N, Binur R, Suhaemi, Anggoro AW. 2017. Review: Biology of the commercially used sea urchin Tripneustes gratilla (Linnaeus, 1758) (Echinoidea: Echinodermata). Ocean Life 1: 1-10. Tripneustes gratilla is a species of sea urchin in shallow tropical waters. The species is economically and commercially important, has ecological value, and prospects as a biological control agent. It is considered as the commercially traded sea urchin. Overexploitation has caused a sharp decline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
(67 reference statements)
2
7
0
3
Order By: Relevance
“…Sonnenholzner et al (2018) suggest that T. depressus has continuous, nondiscrete and synchronous gametogenic activity throughout the year, with two peaks of gonadal development for reproduction. This continuous reproduction pattern with peaks in winter and summer has been reported for other species of the genus such as T. ventricosus off the coast of Florida (McPherson, 1965) and T. gratilla in Madagascar, Kenya and the Philippines (Muthiga, 2005;Toha et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…Sonnenholzner et al (2018) suggest that T. depressus has continuous, nondiscrete and synchronous gametogenic activity throughout the year, with two peaks of gonadal development for reproduction. This continuous reproduction pattern with peaks in winter and summer has been reported for other species of the genus such as T. ventricosus off the coast of Florida (McPherson, 1965) and T. gratilla in Madagascar, Kenya and the Philippines (Muthiga, 2005;Toha et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, both species were observed at 160 m depth; three specimens of T. gratilla on Pukao and one specimen of P. indiana on Apolo. Tripneustes gratilla was reported with a maximum depth of 75 m (Toha et al 2017), so this report extends its known depth range by 85 m. Pseudoboletia indiana is absent from most EIE databases (i.e. review from Fernández et al, 2014, OBIS database), but it was not only observed in the present study but specimens from Rapa Nui were also used for a molecular study of the genus (Zigler et al 2012), so it likely abundant near Rapa Nui.…”
Section: Family Clypeasteridae L Agassiz 1835supporting
confidence: 49%
“…Targeting more economically important species in any such co-culturing venture would further add to the cost reduction benefits. For example, the collector sea urchin Tripneustes gratilla is an important food item in many countries across the world such as the Philippines and South Korea 53 . Whilst not the main focus of this paper we have been successful in culturing T. gratilla , and therefore suggest this species as an alternative to M. globulus when co-culturing corals in future projects.…”
Section: Discussionmentioning
confidence: 99%